The Levels of Zinc, Selenium, Iron and Copper in Preterm Pregnancy do not Differ with those of Healthy Pregnancy: Kadar Seng, Selenium, Besi dan Tembaga pada Kehamilan Prematur tidak Berbeda dengan Kehamilan Sehat - Noroyono Wibowo; Fitriana fitriana (Indonesian Socety of Obstetrics and Gynecology, 2019)
Objective: to compare zinc, selenium, iron and copper levels in maternal serum of normal and preterm pregnancy. Methods: It is a cross sectional study with preterm and normal pregnant woman who will carry delivery in Dr. Cipto Mangunkusumo National Hospital and Budi Kemuliaan Hospital Jakarta from January to April 2017. This study was conducted by comparing the levels of each micronutrient in both groups of subjects. Result: From January until April 2017, there were 53 subjects divided into 30 normal pregnant women and 23 preterm pregnant women. The levels of zinc, selenium iron and copper in preterm pregnancy were 42 µg/dL, 72,39 µg/L, 74 µg/L, and 2144,52 µg/dL. Levels of zinc, selenium, iron and copper in normal pregnancy were 42 µg/dL, 67,27 µg/L, 70,5 µg/L, and 2221 µg/dL. There was no difference in micronutrients level in both groups. Conclusion: This study concluded that there was no difference in zinc, selenium, iron and copper levels in normal and preterm pregnancy. Keywords: pregnancy, zinc, selenium, iron, copper LatarBelakang:Persalinan preterm adalahpersalinansebelumusiakehamilan 37 minggulengkap. Persalinan preterm inimasihmenjadimasalah di seluruhdunia.Padalaporan World Health Organization (WHO), Indonesia mendudukiperingkatkelimanegaradenganpersalinan preterm terbanyakyakni 675.700 persalinanpadatahun 2010.Berbagaifaktordihubungkandenganpenyebabterjadinyapersalinan preterm, termasuksalahsatunyaadalahgangguannutrisiselamakehamilan, terutamaseng, selenium, besidantembaga. Tujuan:Penelitianinimembandingkankadarseng, selenium, besidantembagapada serum maternal ibuhamil normal dan preterm. Metode:Penelitiandilakukandenganujipotong-lintangdengansubjekpenelitianibuhamilbaik preterm maupunaterm yang akanmelaksanakanpersalinan di RSUPN Dr. CiptoMangunkusumodan RS Budi Kemuliaan Jakarta padaJanuarihingga April 2017. Penelitiandilakukandenganmembandingkankadarmasing-masingmikronutrienpadakeduakelompoksubjek. Hasil:DalamjangkawaktuJanuarihingga April 2017 didapatkan 53 subjekpenelitianyakni 30 ibuhamil normal dan 23 ibudengankehamilan preterm. Seluruhsubjekdimasukkandalamanalisis data.Kadar seng, selenium, besidantembagapadaibudengankehamilan preterm secaraberurutanadalah 42 µg/dL, 72,39 µg/L, 74 µg/L, dan 2144,52 µg/dL.Sedangkankadarseng, selenium, besidantembagapadaibuhamil normal secaraberurutanadalah 42 µg/dL, 67,27 µg/L, 70,5 µg/L, dan 2221 µg/dL. Tidakadaperbedaanbermaknakadarmikronutrienpadakeduakelompoksubjek. Kesimpulan: Penelitianinimenyimpulkanbahwatidakadaperbedaankadarseng, selenium, besidantembagapadaibuhamil normal danibudengankehamilan preterm. Kata kunci:kehamilan, seng, selenium, besi, tembaga